Effects of the harmful algal bloom toxin, okadaic acid, on the mechanoreceptors of larval anchoveta (Engraulis ringens) under varying environmental conditions - Pepe-Vargas, Piera; Castro, Leonardo R.; Alves-de-Souza, Catharina; Llanos-Rivera, Alejandra (Frontiers in Marine Science, 2024)
The effect of the combination of marine toxins produced by algal blooms, in conjunction with varying environmental characteristics on organisms in the water column, is a poorly explored research field. Pelagic fish species of commercial importance, such as anchoveta (Engraulis ringens) in central Chile, may be exposed to these combined factors in a climate change scenario. This is observed from documented changes in the length of the upwelling season, frequency of upwelling events, and the increased frequency of atmospheric rivers affecting the southern spawning zone of this species. This study evaluated the integrity of hair cells in neuromasts, mechanosensory organs present in fish larvae, under exposure to different combinations of the algal bloom-produced okadaic acid OA (1 ng ml-1), and two temperature (12 and 14°C), and salinity treatments (historically more frequent: 34 PSU-12°C; expected: 32 PSU -14°C). Viable hair cells were counted in newly hatched larvae from the Biobío region, central Chile. Results showed a significant decrease in the average number of viable hair cells per neuromast (from 6.1 ± 1.6 to 4.0 ± 1.2) under lower salinity treatments (32 PSU) compared to normal conditions. Additionally, a seasonal trend was observed with fewer viable cells (from 7.4 ± 1.2 to 4.4 ± 1.1) as the fish species' reproductive period progressed. The combined effect of OA exposure with modifications in the environmental factors also resulted in a significant decrease of up to 70% in the number of viable hair cells in larvae exposed to OA and high temperatures, indicating damage influenced by the toxin along with a synergistic and/or additive role of temperature. These findings reveal how the lipophilic toxin okadaic acid, produced by harmful algal blooms, interacts with abiotic environmental factors affecting coastal ecologically and socio-economically important organisms. This emphasizes the need to consider multiple factors when studying the effects of marine toxins.